278 Duration of Prescription of Dexamethasone in COVID-19 Pneumonitis. (12th October 2021) - Moen, C
Abstract: Aim: The RECOVERY trial showed the effectiveness of using 10 days of dexamethasone for patients hospitalised with Covid-19 disease who required oxygen or mechanical ventilation while an inpatient. This QIP sought to measure compliance with this recommendation. Method: Live data was obtained using University Hospital Crosshouse's electronic prescribing system (JAC). The audit was limited to patients on Ward 2D, which at time of writing was one of the hospitals COVID 19 wards. The first audit was performed on Friday 13/11/20 at 18:00. All dexamethasone prescriptions had the duration of the prescription assessed (at the time all patients were on oxygen therapy for COVID-19 infection). Patients with a course longer than 10 days with explicit documentation to continue past 10 days were counted as a correct prescription in this audit. For the second cycle results were shared with middle tier doctors working on Ward 2D 16/11/20. Notices were also left on all computers on the ward with the message "Please ensure your patient is only prescribed a total of 10 days of dexamethasone unless an extended course is clinically indicated". A third cycle was carried out 01/12/20. Notices were left on all computers in the combined assessment unit with the same message as above. Results: It found most patients were receiving more than the 10 days due to prescription errors (86%). Teaching on the COVID ward resulted in 83% of the prescriptions being correct. Teaching in the receiving unit of the hospital resulted in no change. Conclusions: Prescriptions of dexamethasone for Covid-19 patients requiring oxygen on ward 2D were found to be longer than the advised 10 days shown to be effective in the Recovery trial. Teaching on the ward was found to be an effective method to decrease prolonged courses of dexamethasone.